Expert consensus on characteristics important or essential for achieving international podium success as an elite endurance runner: a delphi survey - Elvish, T.; Kremer, P.; Trowell, D.; Millet, E. L.; Turner, K. J.; Bonacci, J.; Pickering, C.; Saunders, N. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Current literature identifies biological [1], psychological [2] and social characteristics [2,3] possessed by elite endurance runners. However, there is a lack of consensus on which characteristics are important for achieving podium success as an elite endurance runner. Improved understanding of the biopsychosocial profile of elite endurance-based runners can guide ongoing athlete development and allocation of resources when targeting international podium success. The aim of this study is to understand characteristics experts believe are important or essential for achieving international podium success as an elite endurance runner. METHODS: Fourteen middle distance running (MDR) and 10 long distance running (LDR) experts participated in Round 1 and 12 MDR and eight LDR experts participated in Round 2 of a Delphi survey. Experts included coaches and practitioners who work with elite Australian able-bodied endurance-based runners. Experts were asked to rate, using a Likert scale (range:0= completely irrelevant to 5= essential), how important they believed each characteristic was for achieving international podium success in MDR and LDR. The list of characteristics presented was based on the findings of a systematic review and expert interviews, outcomes of a larger project. Characteristics endorsed as `essential` or `important` by >80% but<60% of experts in Round 1 were taken to Round 2. Characteristics were classified as important if =80% of experts endorsed the characteristic as `essential` or `important` [4]. Consensus was not sought beyond two rounds. RESULTS: Of the 188 biopsychosocial characteristics presented 154 were endorsed or rejected in Round 1, hence 34 characteristics were included in Round 2. After Round 2, 22 MDR related biological, 19 LDR related biological, 30 psychological and 10 social characteristics were endorsed as being important or essential for international podium success. Biological characteristics endorsed by all MDR experts included; capacity to run rounds, maximal aerobic speed, tactical awareness and capacity to recover from training. Biological characteristics endorsed by all LDR experts; capacity to tolerate high training loads, capacity to pace, maximal oxygen uptake, capacity to recover from training, running economy and efficiency. Psychosocial characteristics endorsed by all endurance-based running experts included; ability to cope with pressure, dedication, resilience, self-belief, coach-athlete relationship and training environment. CONCLUSION: Findings highlight the importance of a biopsychosocial approach to the development of elite endurance-based runners. These findings may be useful in continuing to profile elite endurance-based runners to better inform athlete development. Ongoing efforts to use these findings to monitor athlete progression in an effort to differentiate between those who do and do not achieve podium success, is warranted.